2022
DOI: 10.3390/jcm11206025
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and Gustatory Outcomes Including Health-Related Quality of Life 3–6 and 12 Months after Severe-to-Critical COVID-19: A SECURe Prospective Cohort Study

Abstract: Background: Long-term follow-up studies of COVID-19 olfactory and gustatory disorders (OGDs) are scarce. OGD, parosmia, and dysgeusia affect health-related quality of life (HRQoL) and the ability to detect potential hazards. Methods: In this study, 29 patients reporting OGD 1 month after severe-to-critical COVID-19 were tested at 3–6 months and retested at 12 months in case of hyposmia/anosmia. We used Sniffin Sticks Threshold, Discrimination, and Identification (TDI) test, Sniffin Sticks Identification Test (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 60 publications
2
6
0
1
Order By: Relevance
“…The results of the other parts of the test (discrimination and identification) were significantly better, suggesting that if the stimulus is intense enough, incorrect discrimination and identification of odors are less frequent. Similar results have been obtained by other authors, both in patients shortly after a positive COVID-19 test result and in those with ODs lasting more than 4 weeks [ 6 , 14 , 22 , 23 , 24 , 25 , 26 ]. In all studies in which the SST was used to assess OD, the threshold test had the most significant effect on the overall test score.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the other parts of the test (discrimination and identification) were significantly better, suggesting that if the stimulus is intense enough, incorrect discrimination and identification of odors are less frequent. Similar results have been obtained by other authors, both in patients shortly after a positive COVID-19 test result and in those with ODs lasting more than 4 weeks [ 6 , 14 , 22 , 23 , 24 , 25 , 26 ]. In all studies in which the SST was used to assess OD, the threshold test had the most significant effect on the overall test score.…”
Section: Discussionsupporting
confidence: 90%
“…More recent findings by Prem and colleagues indicate that in patients with short-lasting disorders (up to 4 weeks), TS scores correlate well with information from medical interviews, whereas there is a weak correlation between persistent GD and OD [ 26 , 28 ]. Some publications have found a different prevalence of disorders depending on the taste concerned: for example, in the study by Arndal et al, the least recognized taste was bitter [ 14 ], while Singer-Cornelius et al found it was sour [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did not use any taste strips to confirm that, a good correlation between these and reported TD has been described in the past. 2 Moreover, the absence of patients reporting a TD in our population corroborates previous studies 3,4 that show how long-term COVID-19-related TD is much less prevalent than persistent OD.…”
supporting
confidence: 90%
“…El diagnóstico depende de pruebas complementarias (2). Para identificar la anosmia y disgeusia se sugiere una prueba de olfato 16 (SIT16) y una prueba de gustometría (3).…”
Section: Introductionunclassified